SM STRATEGI DAN TAKTIK VISUALISASI INFOGRAFIS DALAM PENYAMPAIAN BERITA PADA AKUN INSTAGRAM: @PINTERPOLITIK - Subria Mamis (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to review infographic visualization strategies and tactics used by @pinterpolitik Instagram accounts and review the perspectives of followers on @pinterpolitik Instagram accounts in delivering news. The type of research used is descriptive qualitative, which describes the phenomenon of infographics on @pinterpolitik Instagram account. This study used content analysis methods, data collected through observation and document studies. The data is analyzed using data reduction, data presentation and conclusions. The results of this study show that the infographic visualization strategy and tactics used by @pinterpolitik Instagram account in delivering news involve three important stages in the strategy, namely formulation, implementation, and evaluation. The formulation stage is the selection of the type of social media used and the ability to search or search for issues. The two stages of implementation are avoiding information that is too long and boring, maximizing aspects of corporate branding or institutional branding, uploading products in prime time hours and using attractive visual content. The third stage of evaluation is to analyze or see from existing data about engagement that occurs on social media accounts @pinterpolitik. In carrying out the infographic visualization of tactics process, @pinterpolitik utilize product that are the main idea to deliver news, namely Indepth, celoteh and video. The perspective of followers on the news delivered by @pinterpolitik account can be seen from the increase in followers over time, this proves that the content presented by the Instagram account @pinterpolitik useful and increase knowledge for readers. Furthermore, the information or news presented has more controversial and political value so that it affects reader interactivity which can be seen through likes, comments and shares on each post.